2016
DOI: 10.1167/iovs.16-20045
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Capillary Density and Foveal Avascular Zone Area Are Age-Dependent: Quantitative Analysis Using Optical Coherence Tomography Angiography

Abstract: SCP and DCP vessel density decreased with increasing age, while FAZ area increased with age. Normal age-matched measurements provide important standardized values that may facilitate management of retinal vascular disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
212
10
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 256 publications
(263 citation statements)
references
References 37 publications
28
212
10
5
Order By: Relevance
“…Furthermore, although we observe significant progression rates over time, the progression rate of perfusion density at the SCP was not different from that at the DCP (P = 0.986), with similar findings observed for the FAZ area (P = 0.053). In normal subjects, the progression rates of both FAZ area and perfusion density between the SCP and DCP were also similar, as described above 10 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, although we observe significant progression rates over time, the progression rate of perfusion density at the SCP was not different from that at the DCP (P = 0.986), with similar findings observed for the FAZ area (P = 0.053). In normal subjects, the progression rates of both FAZ area and perfusion density between the SCP and DCP were also similar, as described above 10 .…”
Section: Discussionsupporting
confidence: 73%
“…In our study, we found that at any given visit, the SCP exhibited perfusion density and FAZ area values that significantly differed from those of the DCP (P < 0.001 for all comparisons). Another previous study analyzed normal subjects with OCT-A and quantified progression rates of perfusion density and FAZ area at the SCP and DCP 10 . They reported that perfusion density decreases at a rate of 0.26% per year at the SCP and 0.27% per year at the DCP.…”
Section: Discussionmentioning
confidence: 99%
“…Gadde et al reported that age did not affect SCP vessel density, 36 while other reports found that SCP vessel density decreased with increasing age. 19, 31, 39, 40 The study by Gadde et al had a relatively small sample size (n = 18) and a younger (< 68 years) age group, which may explain at least in part the differences in the results. Additionally, the impact of SSI on the vessel density measurements was significant and strong (coefficient: 0.29% to 0.37% per unit in multivariate analysis) in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Agemy et al 28 evaluated retinal capillary density in a group of five healthy subjects with ages ranging from 52 to 58 and found a coefficient of variation of less than 7%. Iafe et al 29 found that capillary density declined while the FAZ area expanded with age.…”
Section: Introductionmentioning
confidence: 98%